Formation and evolution of shish‐kebab structure during hot stretching in gel‐spun ultra‐high molecular weight polyethylene fibers with high concentration gel solution. Issue 3 (21st February 2019) - An, Minfang; Lv, You; Xu, Haojun; Li, Yiguo; Wang, Zongbao
Abstract: Formation and evolution of shish‐kebab crystals of gel‐spun ultra‐high molecular weight polyethylene fibers from high concentration gel solution during hot‐stretching process were studied by in situ small‐angle X‐ray scattering and wide‐angle X‐ray diffraction measurements, differential scanning calorimetry, and scanning electron microscopy. We show that the structural evolution process can be divided into three stages, namely, formation of shish‐kebab crystals (stage I), transition of shish‐kebab crystals (stage II), and further transition of fibrillar crystals (stage III). The formation and evolution of shish‐kebab crystals at low stretching temperature were mainly achieved via lamellar fragmentation and crystal slip, while those at high stretching temperature were achieved via stress‐induced melting recrystallization. Furthermore, low stretching temperature is not conducive to the formation and transformation of shish‐kebab crystals, and most of the fibrillar crystals form directly via lamellar fragmentation and crystal slip. However, the fibrillar crystals formed at high stretching temperature are better than those at low stretching temperature due to the partial chain disentanglement. Abstract : Formation and evolution of shish‐kebab crystals of gel‐spun ultra‐high molecular weight polyethylene fibers from high concentration gel solution during hot‐stretching process were studied by in situ small‐angle X‐ray scattering and wide‐angle X‐ray diffraction measurements, differential scanning calorimetry, and scanning electron microscopy.